Pendampingan Pembuatan Kemasan Produk Pada Produk Rengginang Ubi Desa Raba Baka, Kabupaten Dompu - Ernawati, Sri; Humaira, Putri (Welfare : Jurnal Pengabdian Masyarakat, 2023)
Business actors in Raba Baka village do not yet know the importance of packaging for the products they sell, one of which is the rengginang sweet potato business. The method we use is to assist in the manufacture of cassava root and packaging. The results achieved by Rengginan products are made with cassava raw materials, which are the local potential of Raba Baka Village, and contemporary kemsan with standing pouches. We hope that the current products and packaging can increase the selling value of the product so that the income of MSMEs can increase. Activities are carried out in several stages, namely conducting service, selecting partners, and conducting training and development. As a community service, we provide assistance and training regarding the importance of developing product packaging for increasing product sales.